The Dimension of Canadian Younth Unemployment : A Theoretical Explanation - Lazar, Fred; Donner, Arthur (Relations industrielles / Industrial Relations, 1973)
This paper looks beneath the national unemployment numbers to examine in detail the dimension of Canada’s youth unemployment problem. After an outline of the empirical dimensions of youth unemployment in Canada, a theoritical framework is set out to explain the particular characteristics of youth unemployment. Finally, some policy recommendations are presented.